2011
DOI: 10.1680/macr.2011.63.10.763
|View full text |Cite
|
Sign up to set email alerts
|

Fracture properties of geopolymer paste and concrete

Abstract: Geopolymers are an emerging type of cementitious material purported to provide an environmentally friendly alternative to Portland cement-based concrete. This paper reports the results of experimental research on fracture properties (fracture energy and brittleness) of fly ash based geopolymer concrete and paste with various mix parameters. The characteristic length of the geopolymer concrete was approximately three times less than that of ordinary Portland cement (OPC) concrete, due to an increase in tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(78 citation statements)
references
References 13 publications
2
60
0
Order By: Relevance
“…Three identical specimens were tested for each mixture except for mixture GPC2, for which two specimens were tested. The loading rate used in the fracture tests of concrete specimens by previous researchers varied in a considerable range, such as 0.05 mm/min [19], 0.18 mm/min [23] and 0.5 mm/min [24]. A loading rate of 0.18 mm/min was used in the tests of this study.…”
Section: Test Specimens and Testingmentioning
confidence: 99%
“…Three identical specimens were tested for each mixture except for mixture GPC2, for which two specimens were tested. The loading rate used in the fracture tests of concrete specimens by previous researchers varied in a considerable range, such as 0.05 mm/min [19], 0.18 mm/min [23] and 0.5 mm/min [24]. A loading rate of 0.18 mm/min was used in the tests of this study.…”
Section: Test Specimens and Testingmentioning
confidence: 99%
“…Geopolymer concrete is formed by a reaction of silicon and aluminium in byproduct materials such as fly ash, ground granulated blast furnace slag and rice husk ash with an alkaline liquid, which leads to the formation of a cement-like binder [48][49][50]. Numerous studies have been conducted to investigate the mechanical properties and durability of geopolymer concrete to explore its suitability as a replacement for Portland cement concrete and to assess its competitive performance in terms of compressive strength, tensile strength and modulus of elasticity as well as shrinkage, creep, corrosion resistance, sulphate resistance, fire resistance and acid resistance [47,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Low-carbon Materialsmentioning
confidence: 99%
“…Its use is, however, limited by concerns regarding an increased brittleness compared to OPC concrete [10]. Neville & Brooks [11] suggested that cementitious materials are generally brittle in behaviour and are inherently weak in resisting tensile forces.…”
Section: Fibre-reinforced Concretementioning
confidence: 99%